2019
DOI: 10.1002/ange.201810600
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Gels Formed in Deep Eutectic Solvents: Supramolecular Eutectogels with High Ionic Conductivity

Abstract: This paper reports the ability of 1,3:2,4-dibenzylidene-Dsorbitol (DBS), a simple, commercially-relevant compound, to selfassemble as a result of intermolecular non-covalent interactions into supramolecular gels in deep eutectic solvents (DESs). The DESs are based on choline chloride combined with alcohols/ureas -DBS forms gels at a loading of 5% wt/vol. Rheology confirms the gel-like nature of the materials, electron microscopy and X-ray diffraction indicate underpinning nanofibrillar DBS networks and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…The formation of gel was assessed using the tube inversion method and falling ball method (Video S1). The concentrations of the surfactants taken for the formation of each eutectogels are listed in Table . , …”
Section: Methodsmentioning
confidence: 99%
“…The formation of gel was assessed using the tube inversion method and falling ball method (Video S1). The concentrations of the surfactants taken for the formation of each eutectogels are listed in Table . , …”
Section: Methodsmentioning
confidence: 99%
“…A recent development in the field is represented by gels formed using ionic liquids (ionogels or ionic liquid gels) [22][23][24][25] and even, deep eutectic solvents (eutecto gels). 23,[26][27][28][29][30] Thanks to their properties, supramolecular gels have been applied in different fields, like drug delivery systems, 31,32 sensors, [33][34][35] and sorbent systems for the removal of different environmental pollutants. [36][37][38] Among different applications, the use of these soft materials as reaction media has recently gained a raise in interest.…”
Section: Introductionmentioning
confidence: 99%
“…74,75 Inspired by ionic liquid gels that simultaneously possess liquid-like gas transport efficiency and solid-like mechanical properties, 76 soft solid or gels-based DES can also serve as good materials for membrane applications. 77,78 The study of these DES materials is recent, and some results have shown that it is possible to manufacture materials with properties better than those of SLM.…”
Section: Des-based Supported Liquidmentioning
confidence: 99%